Sevoflurane Impairs Short-Term Memory by Affecting PSD-95 and AMPA Receptor in the Hippocampus of a Mouse Model - Yuan Jiao; Hongwu Fan; Kexin Wang; Shan Lu (Behavioural Neurology)
Objective. To explore the effects of sevoflurane on the latency and error times of the passive avoidance and levels of PSD-95 and AMPA receptors in the hippocampus. We evaluated the effects of sevoflurane on short-term memory in adult mice and explored the possible mechanism. Methods. 144 Kunming mice (2-3 months, 30-35 g) were randomly divided into two groups A (n=64) and B (n=80) and received the dark-avoidance (DA) and step-down avoidance (SA) tests, respectively. The groups DA and SA were further divided into control (inhaled 40% O2 2 h) and sevoflurane (3.3% sevoflurane and 40% O2 2 h) subgroups. Before inhalation intervention, all mice were trained to be familiar with the Morris water maze (MWM). According to the test points of behavioral indicators, 8 mice were randomly selected from each subgroup at point 12 h (T1), 24 h (T2), 48 h (T3), and 72 h (T4) after inhalation intervention. The step-through latency and error times were measured in 5 min. After the behavioral test, the mice were killed and the tissues of the hippocampus were taken for hematoxylin and eosin (H&E) staining. The expression level of PSD-95 and AMPA receptors in the hippocampus was detected by immunohistochemistry and Western Blot. The changes of synaptic transmission were measured via electrophysiology analysis of hippocampal slices. Results. The mice in the control subgroups found the platform in a shorter pathway than those in the sevoflurane subgroups during an MWM test. The step-through latency of T1 and T2 in the sevoflurane subgroup was shorter than baseline time, and the error times were increased in 5 min and higher than baseline time when compared with the control subgroup (P<0.05) in the A and B groups. Compared with the control subgroup, the expression level of PSD-95 and AMPA receptors in the hippocampus was decreased at T1 and T2 in the sevoflurane subgroup (P<0.05). The nerve cells were partially swelling. Electrophysiology analysis showed that the levels of PSD-95 and AMPA receptor expression were associated with synaptic transmission. Conclusion. Sevoflurane impaired short-term memory in adult mice by inhibiting the expression of PSD-95 and AMPA receptors in the hippocampus, which led to the decrease in synaptic transmission.